Lethal agent - Mills, Kyle, 1966- (New York : Atria Books, 2019)
ISIS kidnaps a brilliant French microbiologist and forces him to begin manufacturing anthrax. Rapp embarks on a mission to infiltrate the Mexican cartels and track down the ISIS leader and rescue the French microbiologist.
At head of title: Vince Flynn.
Keywords: Rapp, Mitch -- (Fictitious character) -- Fiction; United States. -- Central Intelligence Agency -- Officials and employees -- Fiction; Intelligence officers -- United States -- Fiction; Biological warfare -- Fiction; Bioterrorism -- Prevention -- Fiction; Terrorism -- Prevention -- Fiction; Terrorists -- Fiction; Political corruption -- Fiction; Political fiction; Spy fiction; Political fiction